Biochemical and morphological changes that characterise recovery from necrotising biliary pancreatitis in the opossum. Issue 3 (September 1995) - Rünzi, M; Saluja, A; Kaiser, A; Gerdes, D; Sengupta, A; Steer, M L
Abstract : The events that characterise recovery from severe biliary pancreatitis have not been defined. This study used a reversible model of necrotising pancreatitis, induced by obstructing the opossum common bile pancreatic duct (CBPD), to evaluate this phenomenon. The CBPD of opossums was obstructed with a balloon tipped catheter for five days and then decompressed by removal of the catheter. Recovery was evaluated 0-90 days after relief of obstruction. Serum bilirubin and amylase values rapidly declined, reaching control values 7-14 days after removal of the obstructing catheter. Pancreatic protein and amylase values were transiently increased shortly after relief of obstruction but returned to control values 21 days after decompression. Pancreatic ornithine decarboxylase activity and incorporation of [3H]-thymidine into DNA were transiently increased 14 days after duct decompression suggesting that regeneration occurs at approximately that time. Foci of pancreatic necrosis involved roughly 40% of the gland at time of decompression but these foci gradually disappeared and the gland resembled that of control animals 60 days after decompression. Evidence of fibrosis or collagen deposition in the pancreas was not noted at any time. These studies show that recovery after necrotising biliary pancreatitis occurs comparatively rapidly and the restitution ad integrum occurs. Recovery from necrotising acute pancreatitis in this model is not associated with the development of chronic pancreatitis.